2012
DOI: 10.3109/03009742.2012.729608
|View full text |Cite
|
Sign up to set email alerts
|

The role of monocytes andSLC11A1polymorphisms in the pathogenesis ofChlamydia-induced reactive arthritis

Abstract: The bactericidal activity of monocytes in patients with ReA is lower than that in healthy controls. The SLC11A1 274C/T and 823C/T polymorphisms may be associated with the decreased bactericidal activity of the monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
1
2
Order By: Relevance
“…The exact pathogenesis of the Th1/Th2 imbalance is not understood, but it is not unlikely that genetic factors are involved . Various cytokine gene polymorphisms have been reported and include polymorphisms in monocyte and solute carrier family 11 member A1 (SLC11A1), TNF‐α (‐238) and TNFR polymorphisms …”
Section: Pathogenetic Mechanismscontrasting
confidence: 63%
See 1 more Smart Citation
“…The exact pathogenesis of the Th1/Th2 imbalance is not understood, but it is not unlikely that genetic factors are involved . Various cytokine gene polymorphisms have been reported and include polymorphisms in monocyte and solute carrier family 11 member A1 (SLC11A1), TNF‐α (‐238) and TNFR polymorphisms …”
Section: Pathogenetic Mechanismscontrasting
confidence: 63%
“…19 Various cytokine gene polymorphisms have been reported and include polymorphisms in monocyte and solute carrier family 11 member A1 (SLC11A1), TNF-a (-238) and TNFR polymorphisms. [74][75][76] Finally, Butrimiene et al have suggested that TNF-a production is higher in patients with chronic ReA and, therefore, the Th1 response in chronic ReA is more dominant than that in acute ReA. Interestingly, in this study no differences were reported in the type II response between the patients with chronic and acute ReA.…”
Section: Pathogenetic Mechanismscontrasting
confidence: 41%
“…accordingly, in the last 10 years, several studies on the association of SLC11A1 variants and Ra in different populations have been published 10,[18][19][20][21] . In addition, a possible association between a SLC11A1 promoter polymorphism and Ra severity 22 , or risk for idiopathic arthritis or juvenile rheumatoid arthritis, has been reported 23,24 . However, in a recent meta-analysis performed by archer, et al 9 , only a single significant association was detected between SLC11A1 variants and Ra, namely the Int4 snP (469+14G/C or rs3731865), with an oR: 1.60 (95% CI: 1.20-2.13).…”
Section: Resultsmentioning
confidence: 99%